Government Spending, Legislature Size, and the Executive Veto - Baqir, Reza (IMF Working Papers; Working Paper ;, 2001)
Recent work on the political economy of fiscal policy has asked how budgetary institutions affect fiscal outcomes. But what determines the budgetary institutions? In this paper I consider one such institution: the executive veto. A simple theoretical framework predicts that jurisdictions with more political actors spending from a common pool of tax resources will choose to empower their executives. Using an econometric framework to identify the exogenous variation in the number of districts, I present evidence from a cross-section of local governments in the United States that jurisdictions with more electoral districts are likely to have executives with veto powers.